High-grade Pleomorphic Sarcoma Associated with Metallosis in a Patient with Total Hip Arthroplasty - Campos, Roni Serra; Meohas, Walter; Ferradosa, Artur Shioji; Freire da Costa, Anneliese Fortuna de Azevedo; Guimarães, João Antonio Matheus; Duarte, Maria Eugenia Leite (Revista Brasileira de Ortopedia, 2021)
Although the relationship between hip arthroplasty and the development of sarcoma was first described in the literature about forty years ago, this association is extremely rare. In the present case report, we describe the association between orthopedic implants and soft tissue sarcoma in a 79-year-old man who underwent primary total hip arthroplasty (THA) for coxarthrosis 24 years ago. In the present case report, we describe the clinical evolution and the radiographic and histopathological findings of the lesion. In the intraoperative period of the second revision surgery, loosening of the acetabular and femoral components in association with extensive areas of necrosis and metallosis was evidenced. We performed debridement of the hip and right thigh region and removed the implants. Due to the extent of the lesion and to necrosis, it was not possible to perform a new joint reconstruction. The histopathological diagnosis of high-grade undifferentiated pleomorphic sarcoma associated with extensive areas of metallosis was confirmed in tissue adjacent to the implant. The patient developed pulmonary metastases and died 6 months after the diagnosis. Despite the rarity of this association, sarcomas should be considered in the differential diagnosis of aseptic loosening, especially in the presence of metallosis in the peri-implant tissue. To our knowledge, the 24-year latency period between primary THA and the establishment of a sarcoma diagnosis is one of the longest reported to date.
Keywords: arthroplasty, replacement, hip; hip prosthesis; metals; sarcoma